The Benefit of Mental Skills Training on Performance and Stress Response in Military Personnel - Jensen, Andrew E.; Bernards, Jake R.; Jameson, Jason T.; Johnson, Douglas C.; Kelly, Karen R. (Frontiers in Psychology, 2020)
Mental skills training (MST) has been suggested to reduce stress in civilian and athletic populations; however, whether these techniques and practices transfer to a military population are unknown. Therefore, the purpose of this study was to evaluate two MST programs against a baseline condition, training-as-usual (TAU), during an intense, active-duty, military training environment. Two hundred and three Marines enrolled in the United States Marine Corps’ Basic Reconnaissance Course participated in this effort (n = 203; age = 22.7 ± 3.3 years; height = 178 ± 6.35 cm; weight = 97.7 ± 8.3 kg; Mean ± SD). Each Marine was assigned to one of three groups, Mindfulness-Based Mind Fitness Training (MMFT), General Mental Skills Training (GMST), or TAU. Operational and cognitive performance measures, as well as, physiological metrics were obtained across three training phases (phase 1-3). Furthermore, phase 3 was sub-divided into pre-ambush, ambush and post-ambush time points. Significant group x time interactions were found for the total number of errors committed on the sustained attention response task (p = 0.004); as well as, plasma cortisol (p < 0.0001) and insulin-like growth factor-1 (IGF-1; p < 0.0001). There were mixed results between groups on operational performance tasks with the MST groups tending to perform better than TAU the more time participants had with MST instruction. During ambush, the differences among groups were especially pronounced for measures of information processing that one would expect MST to enhance: coordinates recall, plot time, and plot accuracy (p < 0.001), with improvements ranging from 24.7% to 87.9% for the MST conditions when compared to TAU. These data demonstrate that independent of the specific type of MST program, the fundamental characteristics of stress regulation embedded within each MST program may enhance performance and cognitive function during time of heightened stress.